The nucleosome DNA entry-exit site is important for transcription termination and prevention of pervasive transcription - Hildreth, A Elizabeth (eLife, 2020)
Compared to other stages in the RNA polymerase II transcription cycle, the role of chromatin in transcription termination is poorly understood. We performed a genetic screen in Saccharomyces cerevisiae to identify histone mutants that exhibit transcriptional readthrough of terminators. Amino acid substitutions identified by the screen map to the nucleosome DNA entry-exit site. The strongest H3 mutants revealed widespread genomic changes, including increased sense-strand transcription upstream and downstream of genes, increased antisense transcription overlapping gene bodies, and reduced nucleosome occupancy particularly at the 3’ ends of genes. Replacement of the native sequence downstream of a gene with a sequence that increases nucleosome occupancy in vivo reduced readthrough transcription and suppressed the effect of a DNA entry-exit site substitution. Our results suggest that nucleosomes can facilitate termination by serving as a barrier to transcription and highlight the importance of the DNA entry-exit site in broadly maintaining the integrity of the transcriptome.